Regulatory Role of N6-Methyladenosine (m6A) Modification in Osteoarthritis - Zhai, Ganggang; Xiao, Likang; Jiang, Chenyang; Yue, Songkai; Zhang, Meng; zheng, Jia; Liu, Zeming; Dong, Yonghui (Frontiers in Cell and Developmental Biology, 2022)
Osteoarthritis (OA) is the most common joint disease, usually occurring in middle-aged and elderly people. However, current treatment for OA in its early stages is ineffective, and drug therapy is often ineffective in slowing the progression of the disease. In fact, a deeper understanding of the underlying molecular mechanisms of OA could help us to better develop effective therapeutic measures. N6-methyladenosine (m6A) is a methylation that occurs at the adenosine N6-position, which is the most common internal modification on eukaryotic mRNAs. The role and mechanisms of m6A in mammalian gene regulation have been extensively studied. The “Writer”, “eraser”, and “reader” proteins are key proteins involved in the dynamic regulation of m6A modifications. Recent studies on post-transcriptional regulation alone have shown that m6a modification has an important role in the development of OA. This paper summarizes the specific regulatory processes of M6A in disease and reviews the role of m6A in OA, describing its pathophysiological role and molecular mechanisms, as well as its future research trends and potential clinical applications in OA.